Heat and Pressure Resistance in Escherichia coli Relates to Protein Folding and Aggregation - Li, Hui; Mercer, Ryan; Behr, Jürgen; Heinzlmeir, Stephanie; McMullen, Lynn M.; Vogel, Rudi F.; Gänzle, Michael G. (Frontiers in Microbiology, 2020)
The locus of heat resistance (LHR) confers extreme heat resistance in E. coli. This study explored the role of the LHR in heat and pressure resistance of E. coli, as well as its relationship with protein folding and aggregation in vivo. The role of LHR was investigated in E. coli MG1655 and the pressure resistant E. coli LMM1010 expressing an ibpA-yfp fusion protein to visualize inclusion bodies by fluorescence microscopy. The expression of proteins by the LHR was determined by proteomic analysis; inclusion bodies of untreated and treated cells were also analysed by proteomics, and by fluorescent microscopy. In total, 11 proteins of LHR were expressed: sHSP20, ClpKGI, sHSP, YdfX1 and YdfX2, HdeD, KefB, Trx, PsiE, DegP, and a hypothetical protein. The proteomic analysis of inclusion bodies revealed a differential abundance of proteins related to oxidative stress in strains carrying the LHR. The LHR reduced the presence of inclusion bodies after heat or pressure treatment, indicating that proteins expressed by the LHR prevent protein aggregation, or disaggregate proteins. This phenotype of the LHR was also conferred by expression of a fragment containing only sHSP20, ClpKGI and sHSP. The LHR and the fragment encoding only sHSP20, ClpKGI and sHSP also enhanced pressure resistance in E. coli MG1655 but had no effect on pressure resistance of E. coli LMM1010. In conclusion, the LHR confers pressure resistance to some strains of E. coli, and reduces protein aggregation. Pressure and heat resistance are also dependent on additional LHR-encoded functions.